The Importance of Safety and Health Measures during Construction Stage - Lai, Zhi Yin; Mohd Amir Shazwan, Hashim (2016)
Construction sector in Malaysia has the highest fatality rate among all of the sectors as safety and health measures had always been neglected, all construction sites always full of hazards and accidents and it can happened anywhere and anytime. This issues have been a major problem to the contractors and they need to ensure that the construction workers safe while conducting construction activities instead of putting themself in accidences. The contractor can only curbe this issues when their fully utilized the safety and health measures provided, they can minimize the risk of accidents. Safety is one of the essential elements for a successful project as accidents happened will also affect the project in term of time, cost and quality. Thus, this research was carried out to prove the vitally importance of safety and health measures during construction stage. This research was conducted in Kuala Lumpur area through survey. 37 numbers of construction workers are randomly selected as the respondents who participate in this research. The finding of this study reveals that most of the construction workers aware that safety and health measures are very important and must be provided on their working sites.